Open Innovation as Human Resource Management Reform Strategy: A Case Study in the Xianrenling Tea Company, China - Tang, Cai; Arunberkfa, Dr.Niwet (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
Currents trends in shared economies and globalization through the Internet make it difficult for traditional closed innovation in human resource management to maintain its claim as a valid alternative to open innovation. This difficulty is echoed in the ever-increasing number of companies seeking effective cooperation and collaborative open innovation with other organizations and personnel through two-way flow of resources and two-way transactions of intellectual property. This preference for the open approach to innovation is generally regarded as a demonstration of the voluntary reformation of human resource management and a progressive change in attitude of those who reject closed innovation. This case study of the Xianrenling Tea Company (XTC) investigated the practice of open innovation as one way of reforming the company’s human resource management. The study’s primary aim was to gain insight into, and cast light on, the extent to which the company practiced this form of innovation as well as to ascertain the widest range of inter- agency and environmental factors that impinged on this practice. The study was quantitative in methodology and confined its search for information and data to all relevant documentary evidence. Its secondary aim was to potentially generate the construction of theory relevant to open innovation as reformative human resource management. The study found that XTC applied open innovation in terms of its organizational structure, culture, incentives, talent cross-border thinking and exchanges, facilitative relationships between employer and employees, capital gain motivations, and the overall valuing of employees as human capital and hence of value. These findings lead to the conclusions that companies like XTC gain from the positive, productive, commercial, and social output of open innovation; that further and broader research could potentially have better significance in general than the present case study was able to achieve.